Rural touristification and short-term rentals reshaping tourism geographies: Algarve’s spatial transformations - Cruz, A. R.; Gato, M. A. (Tourism Geographies, 2026)
Tourification led by the expansion of short-term rentals (STR) has become a major driver of spatial and social transformation within contemporary tourism geographies. While scholarship has largely concentrated on urban contexts, little is known about how these dynamics unfold in rural and lowdensity territories. This article examines the diffusion of STR and associated processes of touristification in the Algarve, Portugal, a region historically shaped by coastal mass tourism but now experiencing a reconfiguration of its rural hinterland. Employing a mixed-methods approach that integrates STR registry data (2000–2024), housing and labour market indicators, policy analysis, and field observations, the study identifies the emergence of a dispersed, platform-mediated form of rural touristification. The results reveal increasing housing pressure, rising property values, and a pronounced tertiarisation of rural economies, accompanied by governance challenges from limited institutional capacity and weak regulatory enforcement. By contrasting these findings with evidence from urban STR research, the article argues that rural touristification represents a distinct process—marked less by direct physical displacement and more by the gradual transformation of everyday life, social practices, and community structures. These insights extend understandings of tourism-led spatial change and underscore the necessity of place-sensitive regulatory frameworks that reconcile tourism development with sustainability.